Oil Pollution Risk Mitigation and MARPOL Annex I Compliance Practices Aboard Tanker Vessels: An Indonesian Seafarer Perspective - Chanra Purnama; Tri Cahyadi; Aditya Rinaldi (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
MARPOL Annex I constitutes the international community's primary regulatory instrument for preventing operational oil pollution from ships, mandating specific onboard procedures for oil record book keeping, bilge water management, and slop handling that tanker vessel officers and ratings are expected to implement as routine operational practice. This study investigates the quality of MARPOL Annex I compliance practice and oil pollution risk mitigation understanding among Indonesian seafarers serving aboard tanker vessels, examining the gap between regulatory knowledge, procedural practice, and risk mitigation orientation through a qualitative design. Data were collected between April 2025 and April 2026 from twenty-six participants comprising active tanker vessel seafarers, shipping company technical managers, and STIP Jakarta Marine Engineering lecturers through focus group discussions and semi-structured interviews. Thematic analysis, cross-group comparison, and narrative synthesis were applied. Findings reveal that procedural MARPOL Annex I compliance is broadly maintained for documentation-visible procedures such as oil record book entries but substantially weaker for operationally complex procedures such as oily water separator management and slop handling, where the gap between documented and actual practice is most pronounced. Cross-group analysis reveals a technical knowledge deficit in the environmental chemistry and risk pathway dimensions of oil pollution rather than merely its procedural regulatory dimension, indicating that compliance practice is predominantly deterrence-driven rather than ecologically grounded. The study contributes a competency profile of MARPOL Annex I risk mitigation practice among Indonesian tanker seafarers and provides curriculum-actionable evidence for STIP Jakarta.